Cognition, emotion, and arithmetic in primary school: A cross‐cultural investigation. (June 2018) - Rodic, Maja; Cui, Jiaxin; Malykh, Sergey; Zhou, Xinlin; Gynku, Elena I.; Bogdanova, Elena L.; Zueva, Dina Y.; Y. Bogdanova, Olga; Kovas, Yulia
Abstract : The study investigated cross‐cultural differences in variability and average performance in arithmetic, mathematical reasoning, symbolic and non‐symbolic magnitude processing, intelligence, spatial ability, and mathematical anxiety in 890 6‐ to 9‐year‐old children from the United Kingdom, Russia, and China. Cross‐cultural differences explained 28% of the variance in arithmetic and 17.3% of the variance in mathematical reasoning, with Chinese children outperforming the other two groups. No cross‐cultural differences were observed for spatial ability and mathematical anxiety. In all samples, symbolic magnitude processing and mathematical reasoning were independently related to early arithmetic. Other factors, such as non‐symbolic magnitude processing, mental rotation, intelligence, and mathematical anxiety, produced differential patterns across the populations. The results are discussed in relation to potential influences of parental practice, school readiness, and linguistic factors on individual differences in early mathematics. Statement of contribution What is already known on this subject? Cross‐cultural differences in mathematical ability are present in preschool children. Similar mechanisms of mathematical development operate in preschool children from the United Kingdom, Russia, and China. Tasks that require understanding of numbers are best predictors of arithmetic in preschool children. What does this study add? Cross‐cultural differences in mathematical ability become greater with age/years of formal education. Similar mechanisms of mathematical development operate in early primary school children from the United Kingdom, Russia, and China. Symbolic number magnitude and mathematical reasoning are the main predictors of arithmetic in all three populations.